THE ROLE OF INTERNATIONAL LEGAL ACTS IN THE PROTECTION OF CHILDREN IN AREAS OF ARMED CONFLICT - Sabina Xudaykulova (Academia Science Repository, 2023)
The protection of children’s rights in areas of armed conflict is also of particular importance to international mechanisms in this area as a humanitarian problem of relations on the world’s policy scene. The article discusses the legal basis for protecting the rights of children in areas of armed conflict—declarations, documents, agreements, pacts, and some of the resolutions—and reveals them with examples and legal norms.